Prevalência das alterações eletrocardiográficas e discussão quantitativa do eletrocardiograma normal do Projeto Teleminas Saúde - Brito, Franciele Guimarães de (2013)
The electrocardiogram (ECG) is generally used in order to follow and detect heart diseases, putting forward that cardiovascular pathologies being one of the leading causes of death in Brazil. Increasingly morbidity and mortality related to cardiovascular events leads recently to great impact on public health. Some countries, including Brazil, have been using the capabilities of telemedicine to provide health care in particular situations for which the access to publich health services is a critical factor, including the context of cardiovascular diseases. Minas Gerais province, for example, has started since 2006 a telecardiology system, part of Teleminas Saúde project, that already covers 70% of the population. Several quirks can interfere in the conduction of the electrical impulse and, consequently, change the ECG. Thus, in the interpretation and clinical ECG analysis must take into account numerous factors such as the ethnic compositions of diverse populations, gender, age. This thesis discusses the main changes in electrocardiographic in Teleminas Saúde, quantifies the normal ECG and investigates features of the population that could influence the amplitude values of the normal electrocardiogram. The quantification of the normal ECG and ECG were obtained through major changes of project data base Teleminas health, the sample was composed of 4000 individuals and after the exclusion, according to the criteria adopted, 1113 examinations within the bounds of normal and 1609 pathological. These findings were compared to patterns arising from the clinical literature, so that relevant differences were noticed. It was also concluded that age and gender could influence the amplitudes of the normal ECG intervals and waves.